2010
DOI: 10.1016/j.chemgeo.2010.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Proton and cadmium adsorption by the archaeon Thermococcus zilligii: Generalising the contrast between thermophiles and mesophiles as sorbents

Abstract: Adsorption by microorganisms can play a significant role in the fate and transport of metals in natural systems. Surface complexation models (SCMs) have been applied extensively to describe metal adsorption by mesophilic bacteria, and several recent studies have extended this framework to thermophilic bacteria. We conduct acid-base titrations and batch experiments to characterise proton and Cd adsorption onto the thermophilic archaeon Thermococcus zilligii. The experimental data and the derived SCMs indicate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Daughney et al (2010) normalized many of these previous measurements to enable direct comparison in an effort to discern if thermophilic microbes have different adsorptive behavior under mesophilic conditions. Their work found that thermophilic bacteria tend to have a lower adsorptive capacity than mesophiles at 25°C.…”
Section: Introductionmentioning
confidence: 99%
“…Daughney et al (2010) normalized many of these previous measurements to enable direct comparison in an effort to discern if thermophilic microbes have different adsorptive behavior under mesophilic conditions. Their work found that thermophilic bacteria tend to have a lower adsorptive capacity than mesophiles at 25°C.…”
Section: Introductionmentioning
confidence: 99%
“…All of the bacteria studied by Ginn and Fein displayed similar extents of proton and Cd adsorption, with the exception of the acidophile, Acidophilium angustum , which exhibited significantly lower proton buffering and metal adsorption capacities than the other species. Daughney et al also examined an archaea, Thermococcus zilligii , that exhibited an order of magnitude lower site concentrations and significantly less Cd adsorption capabilities than most bacteria. , In contrast, the acidophile Thiobacillus ferrooxidans exhibits buffering capacity across a wide pH range, more similar to other bacterial species than to A. angustum . The buffering capacities of other acidophilic bacterial species need to be studied before a general pattern, if any exists, can be discerned.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have shown that the extent of adsorption is dependent on environmental conditions such as pH, ionic strength, and the sorbate/sorbent ratio. Prior studies have developed a variety of surface complexation models (SCMs) to describe ion adsorption to bacteria or iron oxide minerals (Dzombak and Morel, 1990;Cox et al, 1999;Yee and Fein, 2001;Spadini et al, 2003;Peacock and Sherman, 2004;Burnett et al, 2006a;Daughney et al, 2010).…”
Section: Introductionmentioning
confidence: 99%